EXPERIENTIAL MARKETING, BRAND TRUST DAN PENGARUHNYA TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING - yahya, Yahya (Fakultas Ekonomi Universitas PGRI Adi Buana, 2019)
Consumers satisfaction become the target and goal of every business that is done, the highest form of satisfaction is customer loyalty. To increase customer satisfaction the company required to create a marketing strategy and build brand trust with consumers. This study is aimed to analyze the influence of experiential marketing of sense, feel, think, act, and relate to customer satisfaction and loyalty, analyze the influence of brand trust on customer satisfaction and loyalty, and analyze the effect of satisfaction on consumer loyalty. The population of this study was smartphone users in plaza Marina Surabaya, a questionnaire instrument is used and the samples that is used by 120 respondents in this research. Data analysis techniques with Partial Least Square (PLS) analysis with the help of smart software PLS. The results showed that experiential marketing of sense, think, and act has no significant effect on satisfaction, whereas feel and relate has a significant effect on satisfaction; Brand trust has a significant effect on satisfaction; Experiential marketing of sense and feel has a significant effect on consumer loyalty, and variables think, act and relate have no significant effect on consumer loyalty; Brand trust has a significant effect on consumer loyalty; and satisfaction has a significant effect on consumer loyalty.